2019
DOI: 10.1111/nep.13629
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and dialysis quality of care

Abstract: Aim Lower socioeconomic status (SES) has been associated with increased dialysis mortality. This study aimed to determine if the quality of care (QOC) delivered to dialysis patients varied by SES. Methods All non‐Indigenous adults commencing haemodialysis (HD) or peritoneal dialysis (PD) registered with the Australia and New Zealand Dialysis and Transplant Registry between 2002 and 2012 were included. Each patient's location at dialysis start was classified into SES quartiles of advantaged to disadvantaged. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(76 reference statements)
3
2
0
Order By: Relevance
“…In our study, the MA recipient group demonstrated non-inferior results of clinical indicators compared to the NHI beneficiary group such as lower proportion of hypertension or diabetes, better nutritional status with higher serum albumin, or plasma hemoglobin. Our finding is similar to that found in the recent studies performed in Australia [21]. Krishnasamy et al [21] demonstrated in their article that low SES adversely affects dialysis survival in Australia [15], but SES had minimal impact on biochemical parameters or dialysis adequacy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the MA recipient group demonstrated non-inferior results of clinical indicators compared to the NHI beneficiary group such as lower proportion of hypertension or diabetes, better nutritional status with higher serum albumin, or plasma hemoglobin. Our finding is similar to that found in the recent studies performed in Australia [21]. Krishnasamy et al [21] demonstrated in their article that low SES adversely affects dialysis survival in Australia [15], but SES had minimal impact on biochemical parameters or dialysis adequacy.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is similar to that found in the recent studies performed in Australia [21]. Krishnasamy et al [21] demonstrated in their article that low SES adversely affects dialysis survival in Australia [15], but SES had minimal impact on biochemical parameters or dialysis adequacy. They suggested that low SES may increase mortality due to predialysis factors and other variables such as health-related behaviors, lifestyle, and literacy.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicate that total health literacy does not differ signi cantly with age, gender, education level, and economic level, similar to the ndings of Krishnasamy et al (2020) on socioeconomic status and quality of dialysis care [10]. A possible reason is that most of the PD groups in our study are individuals living in urban areas, and they have relatively high knowledge levels and economic levels.…”
Section: Discussionsupporting
confidence: 79%
“…Individuals in Australia have shown that all patients have a KT/V of 1.3 and higher, which shows better results than the present study. This difference could be due to differences in the type of study, differences in sample size, and better services provided in the centers [23]. The different cut-off points used to determine optimal dialysis adequacy in different countries can be an important factor influencing dialysis adequacy, so that in older guides, especially in developing countries, especially in the EMRO, KT/V>1.2 defined as optimal dialysis adequacy but in developed countries KT / V >1.4 to 1.7 are considered as adequate dialysis adequacy [24,25].…”
Section: Meta-regressionmentioning
confidence: 99%